Prolog . Prolog . Prologue . Пролог - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The life of Anatolia Smykov, chairman of the agricultural cooperative "Plemzavod Alma-Ata." Contributors: Frumkin, Grigorii (Anchor) Жизнь Анатолия Ивановича Смыкова, председателя правления сельскохозяйственного кооператива "Племзавод Алма-Аты". Создатели: Фрумкин, Григорий (Ведущий/Ведущая)